2012
DOI: 10.1186/1471-2164-13-95
|View full text |Cite
|
Sign up to set email alerts
|

The construction of a high-density linkage map for identifying SNP markers that are tightly linked to a nuclear-recessive major gene for male sterility in Cryptomeria japonica D. Don

Abstract: BackgroundHigh-density linkage maps facilitate the mapping of target genes and the construction of partial linkage maps around target loci to develop markers for marker-assisted selection (MAS). MAS is quite challenging in conifers because of their large, complex, and poorly-characterized genomes. Our goal was to construct a high-density linkage map to facilitate the identification of markers that are tightly linked to a major recessive male-sterile gene (ms1) for MAS in C. japonica, a species that is importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 62 publications
0
53
1
Order By: Relevance
“…Near 94% of the markers could be assigned to LGs and 60% could be positioned in the final maps (Table 1, Figure 1, Figure 2 and Additional file 3). The lower percentage of markers positioned when compared with other highly saturated maps [46] is due to the use of SAMPLs only scoring in one of the mapping progenies, as revealed by the low percentage of positioned SAMPLs (Table 1). When we discard SAMPLs scored only in one or the two mapping progenies, the percentage of SAMPL markers positioned in the parental maps increases to 65.3% for C14 and 72.1% for C15.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Near 94% of the markers could be assigned to LGs and 60% could be positioned in the final maps (Table 1, Figure 1, Figure 2 and Additional file 3). The lower percentage of markers positioned when compared with other highly saturated maps [46] is due to the use of SAMPLs only scoring in one of the mapping progenies, as revealed by the low percentage of positioned SAMPLs (Table 1). When we discard SAMPLs scored only in one or the two mapping progenies, the percentage of SAMPL markers positioned in the parental maps increases to 65.3% for C14 and 72.1% for C15.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, new technologies have been developed for high throughput detection and genotyping of SNPs reducing the cost of assays [41,42]. Thus, highly saturated genetic linkage maps can be constructed even for species with large and un-sequenced genomes like conifers [21,43-46]. …”
Section: Introductionmentioning
confidence: 99%
“…Sixty-four of these loci Genome scan for adaptive genes in Cryptomeria japonica Y Tsumura et al were successfully mapped on the C. japonica linkage map, and their distribution was studied ( Figure 5, Moriguchi et al, 2012). The numbers of mapped outlier loci in each LG varied substantially.…”
Section: Outlier Locimentioning
confidence: 99%
“…The figure shows plots of marker position (based on 1255 mapped SNPs or the other DNA markers; Moriguchi et al, 2012) in cumulative centiMorgans (cM) versus (a) Bayes factor (log 10 ), as determined by BayeScan analysis, (b) the probability that the locus is an outlier as judged by the F ST -based test (Beaumont and Nichols, 1996) and (c) F-statistic value, F ST . Vertical dashed lines demarcate the 11…”
Section: Detection Of Outlier Locimentioning
confidence: 99%
“…Similar examples of gene or miRNA atlas can be found in fruit trees, for their response to water stress (Bassett et al, 2014;Eldem et al, 2012) or during winter dormancy (Falavigna et al, 2014). These genomic resources combined with high-density genetic maps constructed for many forest tree species as in eucalyptus (Kullan et al, 2011;Neves, Mamani, Alfenas, Kirst, & Grattapaglia, 2011), maritime pine (Chancerelle et al, 2013), P. abies (Lind et al, 2014), Populus (Berlin, Lagercrantz, von Arnold, € Ost, & R€ onnberg-W€ astljung, 2010; Muchero et al, 2015), Cryptomeria japonica (Moriguchi et al, 2012), constitute a major basis to study the genetic determinants involved in the architectural development of trees. A recent study reported two high-resolution genetic maps constructed using a SNPs array genotyped on a large size pedigree , which has been useful to identify putative candidate genes underlying QTLs (Bartholomé, Mabiala, et al, 2015).…”
Section: Genetics and Genomics Of Tree Growth And Architectural Traitmentioning
confidence: 92%